(untitled) (Medical Forum Monthly, 2023)
Objective: To evaluate the influence of BMI on Nerve Conduction Velocity (NCV), particularly in the peripheral sensory (ulnar) and motor (ulnar and peroneal) nerves of the upper and lower limbs among healthy individuals. As we know NCV is affected even by physiological factors. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Physiology department of Baqai Medical University, Karachi from January 2017 to July 2017. Materials and Methods: Subjects included in this study were 500 healthy adult male and females of Gadap town, Karachi, age ranges between 18-45years. Power Lab was used to record the NCV after stimulation of ulnar and peroneal nerve at wrist and at lateral aspect of knee respectively. Obtained data and basic parametric values were calculated by using the ‘Statistical package for Social science’ (SPSS) software version 22.0. Results: Results showed that, Ulnar sensory nerve have highest mean in obese class, than in overweight and among underweight samples, (p=< 0.01). It showed that, there were significant mean differences in ulnar sensory nerve with respect to BMI, Ulnar motor nerve were also found higher among obese class samples but these results were statistically insignificant, Peroneal motor nerves gave high mean among normal BMI samples, and underweight samples, these results were found statistically significant (p=<0.02). Conclusion: The study showed inverse relationship of ulnar sensory, ulnar motor and peroneal motor nerve conduction velocity with body mass index (BMI).